Paleoseismological investigation along the back thrust bounding the northern limb of Janauri Anticline, NW Himalaya, India - Girish Ch Kothyari; Neha Joshi; Sambit Prasanajit Naik; Ajay Kumar Taloor; Raj Sunil Kandregula; Senjuti Nandy; Charu C. Pant (Quaternary Science Advances, 2023)
Regardless of numerous paleoseismological studies along the active front of the Himalayas, it still lacks precision with respect to earthquake recurrence, rupture, slip mechanism, etc. which hinders understanding of the region's seismic hazards. Considering the seismic hazard posed by the previous Himalayan earthquakes, for instance, from Kashmir, Chamba, Kumaun-Garhwal, Nepal, etc., it becomes vital to identify the seismogenic structures and length of rupture that might be affected in the near future. In the present study, the paleoseismological investigation is carried out along the ∼150 km long Back Thrust (BT) of Himalayan Frontal Thrust bounding the northern limb of Janauri Anticline (JA) in northwest frontal Himalaya. By taking advantage of the optically stimulated luminescence (OSL) dating technique, the present study reports three newly identified seismic events along the BT i.e. 535-1269 AD Event I, 1447–1636 AD Event II, and 1660–1929 AD Event III. Our findings at Palahta locality of Punjab state complement, i.e., 1447–1636 AD (Event II), the effectiveness of previously identified more recent earthquake (MRE) at Hajipur, which further suggest the rupture length of ∼97 km along BT. The other results on the timing of seismic events (Event I and Event III) are well thought out and considered here as independent. Such independent events tend to fill an important gap in the database and provide us an opportunity to explore the paleoseismic events in more detail along the seismogenic structures of the Himalayas. Such a well-established database would assist in better seismic hazard estimation and will directly influence the long-term planning for infrastructure development in the regions like the Himalayas.